Electrochemical behaviour of dopamine at covalent modified glassy carbon electrode with l-cysteine: preliminary results - Martínez-Huitle,Carlos Alberto (2009)
The surface of glassy carbon (GC) electrode has been modified by oxidation of L-cysteine. The covalent modified GC electrode with L-Cysteine has been studied, according the supporting electrolyte used. Favourable interactions between the L-cysteine film and DA enhance the current response compared to that at the Nafion GC and bare GC electrodes, achieving better performances than those other electrodes. This behaviour was as result of the adsorption of the cysteine layer film, compact and uniform formation; depending on L-cysteine solution (phosphate buffer or chloridric acid supporting electrolyte) used for modifying GC surface. In cyclic voltammetric measurements, modified electrodes can successfully separate the oxidation/reduction DA peaks in different buffer solutions, but an evident dependence in the response was obtained as function of pH and modified electrode. The modified electrode prepared with L-cysteine/HCl solution was used to obtain the calibration curve and it exhibited a stable and sensitive response to DA. The results are described and discussed in the light of the existing literature.